Prevention and Treatment of Frequent Respiratory Diseases in Children With Weakened Immune Systems - O. V. Kladova (LLC "Diagnostics and Vaccines", 2016)
We described the results of Arbidol application for ARD prevention and treatment. It is proved that application of Arbidol in the period before the growth of influenza and other ARD morbidity helped to decrease the number of cases of morbidity among sickly children and children with pathology of upper and lower respiratory ways. Therapy with Arbidol decreases fever duration, intoxications and shortens periods of catarrhal inflammation in children with ARD.